A global registry of fractional flow reserve (FFR)–guided management during routine care: Study design, baseline characteristics and outcomes of invasive management. Issue 4 (14th March 2020) - Schampaert, Erick; Kumar, Gautam; Achenbach, Stephan; Galli, Stefano; Tanaka, Nobuhiro; Teraphongphom, Tarn; Ginn, Greg; Zhang, Zhen; Somi, Samer; Amoroso, Giovanni; Brueren, Guus; Krasnow, Joshua; et al.
Abstract: Background: The use and clinical outcomes of fractional flow reserve (FFR)–guided revascularization in patients presenting with either stable coronary artery disease (CAD) or an acute coronary syndrome (ACS) in daily clinical practice are uncertain. Objective: To prospectively characterize the frequency of the change in treatment plan when FFR is performed compared to the initial decision based on angiography alone and procedure‐related outcomes. Methods: We undertook a prospective, multicenter, multinational, open‐label, observational study of coronary physiologic measurements during clinically indicated coronary angiography. The treatment plan, including medical therapy, PCI or CABG, was prospectively recorded before and after performing FFR. Adverse events were pre‐defined and prospectively recorded per local investigators (PRESSUREwire; ClinicalTrials.gov identifier: NCT02935088). Results: Two thousand two hundred and seventeen subjects were enrolled in 70 hospitals across 15 countries between October 2016–February 2018. The mean FFR (all measurements) was 0.84. The treatment plan based on angiography‐alone changed in 763/2196 subjects (34.7%) and 872/2931 lesions (29.8%) post‐FFR. In the per‐patient analysis, the initial treatment plan based on angiography versus the final treatment plan post‐FFR were medical management 1, 350 (61.5%) versus 1, 470 (66.9%) ( p = .0017); PCI 717 (32.7%) versus 604 (27.5%) ( p = .0004); CABG 119 (5.4%) versus 121 (5.5%) ( p = .8951). The frequency of intended revascularization changed from 38.1 to 33.0% per patient ( p = .0005) and from 35.5 to 29.6% per lesion ( p  < .0001) following FFR. Conclusions: On an individual patient basis, use of FFR in everyday practice changes the treatment plan compared to angiography in more than one third of all‐comers selected for physiology‐guided managements. FFR measurement is safe, providing incremental information to guide revascularization decisions.